2019
DOI: 10.1002/jsfa.9966
|View full text |Cite
|
Sign up to set email alerts
|

Ozone technology to reduce zearalenone contamination in whole maize flour: degradation kinetics and impact on quality

Abstract: BACKGROUND Maize is one of the most important cereals. It is used for different purposes and in different industries worldwide. This cereal is prone to contamination with mycotoxins, such as zearalenone (ZEN), which is produced mainly by Fusarium graminearum, F. culmorum and F. equiseti. Toxin production under highly moist conditions (aw > 0.95) is exacerbated if there are alternations between low temperatures (12–14 °C) and high temperatures (25–28 °C). Even if good production practices are adopted, mycotoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 54 publications
(103 reference statements)
1
11
0
1
Order By: Relevance
“…Ozone reduces the toxicity of ZEN by forming degradation ozonolytic products which are less toxic than the original mycotoxin [229]. The reaction rate constant and degradation rate of ZEN increased with ozone concentration and treatment time [228] and this ZEN degradation by ozone followed first-order kinetic [230]. A study by Rogowska et al [1] has suggested 83.9% ZEN degradation with the use of 10% hydrogen peroxide at 30 • C for 16 h. Su et al [23] have also suggested the potential ability of vitamin C to reduce the toxicity of ZEN in animal models.…”
Section: Degradation Kineticsmentioning
confidence: 95%
“…Ozone reduces the toxicity of ZEN by forming degradation ozonolytic products which are less toxic than the original mycotoxin [229]. The reaction rate constant and degradation rate of ZEN increased with ozone concentration and treatment time [228] and this ZEN degradation by ozone followed first-order kinetic [230]. A study by Rogowska et al [1] has suggested 83.9% ZEN degradation with the use of 10% hydrogen peroxide at 30 • C for 16 h. Su et al [23] have also suggested the potential ability of vitamin C to reduce the toxicity of ZEN in animal models.…”
Section: Degradation Kineticsmentioning
confidence: 95%
“…The exposure time to ozone is an important factor that determines the rate of mycotoxin degradation in grains [ 223 ]. The use of ozone (O 3 ) in the degradation of mycotoxins was reported in several papers [ 223 , 227 , 228 , 229 , 230 , 231 ]. It is successful in the degradation of AFB1 and AFG1.…”
Section: Bio-acceptable Solutions For Fungal Control and Detoxification Of Mycotoxinsmentioning
confidence: 99%
“…Ozonation is a simple technology, which does not leave harmful residues after application. The use of O 3 in the degradation of several mycotoxins has been reported in many papers [ 89 , 90 , 91 , 92 , 93 ]. Ozone is used as an oxidizing agent to disinfect cereals, vegetables, and fruits, or to detoxify mycotoxins [ 89 ].…”
Section: Systems For the Control Of Mycotoxins In Feed And Foodmentioning
confidence: 99%
“…As reported above, ozonation is a chemical mean for food/feed processing, that has been used on many kinds of products or intermediates. Most of the reviewed experiments (81%) were carried out on cereals, in particular wheat and corn, and their derivatives such as flour [ 90 , 91 , 121 , 128 , 131 , 132 ], malting [ 122 ], and co-products like pasta and semolina [ 92 ]. Another large percentage of studies (19%) was conducted on dried fruits/seeds (in particular peanuts and pistachios).…”
Section: Mycotoxin Detoxification In Food and Feed By Ozonementioning
confidence: 99%